2001
DOI: 10.1042/cs20010183
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic peptide: is it a predictor of cardiomyopathy in cirrhosis?

Abstract: Subtle cardiac abnormalities have been described in patients with cirrhosis. Natriuretic peptide hormones have been reported to be sensitive markers of early cardiac disease. We postulate that plasma levels of N-terminal pro-atrial natriuretic peptide and brain natriuretic peptide could be used as markers of cardiac dysfunction in cirrhosis. The aim of the study was to evaluate the levels of N-terminal pro-atrial natriuretic peptide and brain natriuretic peptide and their relationship with cardiac structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
1
36
0
1
Order By: Relevance
“…Importantly, these cardiac changes reverse 9 to 12 mo after liver transplantation, suggesting that the diseased liver rather than the cause of liver disease (e.g., alcohol) is responsible for the cardiac dysfunction (36). Cardiac dysfunction also may explain the elevated plasma natriuretic peptide level that has been observed in some but not all patients with cirrhosis, despite reduced central venous pressure (38). In one study of 52 decompensated patients with cirrhosis, natriuretic peptide level correlated with the Child-Pugh score and the ventricular wall thickness (39).…”
Section: Cardiac Dysfunctionmentioning
confidence: 93%
“…Importantly, these cardiac changes reverse 9 to 12 mo after liver transplantation, suggesting that the diseased liver rather than the cause of liver disease (e.g., alcohol) is responsible for the cardiac dysfunction (36). Cardiac dysfunction also may explain the elevated plasma natriuretic peptide level that has been observed in some but not all patients with cirrhosis, despite reduced central venous pressure (38). In one study of 52 decompensated patients with cirrhosis, natriuretic peptide level correlated with the Child-Pugh score and the ventricular wall thickness (39).…”
Section: Cardiac Dysfunctionmentioning
confidence: 93%
“…Brain natriuretic peptide, a sensitive and useful marker for early stage heart disease, has been found to be elevated in some preascitic but most of ascitic cirrhotic patients [27][28][29]. Henriksen and colleagues [26] found that both pro-BNP (a propeptide of BNP) and BNP elevations correlated with the severity of cirrhosis as well as the degree of cardiac dysfunction.…”
Section: Serum Markersmentioning
confidence: 99%
“…Moreover, these correlate with the stage of the liver disease and may show the severity of myocardial dysfunction and ventricular hypertrophy. Despite these favorable features BNP and pro-BNP may not be able to indicate the hyperdynamic circulation [56,57]. These biomarkers have also been shown to be helpful in the screening of CCM [58].…”
Section: Laboratory Markersmentioning
confidence: 99%